Frequency of Vitamin D Deficiency and its Association with CP Class in Cases of Liver Cirrhosis - Zoha Nasir, Muhammad Usaid Khan, Hina Batool, Naveed Nayyer, Jalil Iqbal, Muhammad Zubair, (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: To find out the frequency of vitamin D deficiency and its association with CP class in cases of liver cirrhosis. Study Design: Cross sectional study. Place and Duration: Bahawal Victoria Hospital, Bahawalpur (From September 2021 to March 2022). Methodology: Total 195 cirrhotic patients of any etiology, 20-40 years of age both male and female were selected. Vitamin D deficiency and its association with CP class was assessed. Results: Mean age of cirrhotic patients was 38.46 ± 11.383 years. Out of 195 patients, vitamin D was deficient in 83 (43%) patients. Vitamin D deficiency was found in CP class A, B and C 7 (7.78%) patients, 13 (44.83%) patients and 63 (82.89%) patients respectively. CP class had significant (P = 0.000) association with vitamin D deficiency. Conclusion: In this study, higher proportion of cirrhotic patients had deficient levels of vitamin D. Most of the patients were between 20-40 years. A higher number of male patients had deficient levels of vitamin D. It is also concluded that vitamin D deficiency is significantly associated with CP class. Keywords: liver cirrhosis, CP class, vitamin D, hepatic osteodystrophy.